ЎЗБЕКИСТОНДА ТУРИЗМ СОҲАСИДАГИ ИСЛОҲОТЛАР ТАЛАБАЛАРНИНГ ТУРИСТИК МАДАНИЯТИНИ ТАКОМИЛЛАШТИРИШ ОМИЛИ СИФАТИДА - Нафасов, Д.Ш. (FAN va JAMIYAT, 2018)
The article is devoted to the description of current reforms in the field of tourism, it is stated that tourism laws, Decrees and Resolutions of the President of the Republic of Uzbekistan are important documents in improving the tourist culture of students at higher educational establishments.